Penyidikan Kasus Persetubuhan Terhadap Anak Sebagai Pelaku (Studi di Kepolisian Resort Kota Batu) - Raras Verawati; Sidik Sunaryo; Yaris Adhial Fajrin (Indonesia Law Reform Journal, 2022)
Crime of decency cannot be measured by age or characteristics because anyone can do it, including children. Actions that can be categorized as violating decency include intercourse. The crime of sexual intercourse is regulated in the Criminal Code articles 286-288 and regulated in the Child Protection Law Article 81. Sexual intercourse with children at the Batu Police is still some cases. This study aims to determine a series of investigators' actions to find and collect evidence of cases of sexual intercourse with children as perpetrators by the Batu City Police. The research method used is juridical sociology by looking at the law as human behavior in life. Batu City Police research location. From the results of this study, it can be concluded that a series of investigators' actions in investigating cases of sexual intercourse with children as perpetrators at the Batu City Police in general can be said to have not been maximized, there are still obstacles in practice such as (1) the time period from the report to the investigation stage cannot be ascertained, (2) there are obstacles in the examination of victims, some victims are reluctant to provide information, (3) the examination of witnesses becomes an obstacle because the crime of sexual intercourse is carried out in places that are rarely or known to witnesses, (4) examination of child suspects in practice the police have not used the familial method, (5) the arrests made by the investigators of the Batu City Resort Police were judged not to be in accordance with the provisions of the SPPA Law Article 30 paragraph (4) and strengthened by Perkap No. 8 of 2009 Article 21 letter d, (6) in the Bapas examination there was an error in the case file provided by the police and in the collection there were still obstacles, (7) lack of knowledge about the importance of the post-mortem this could have an impact on the results of the investigation.